2006
DOI: 10.1007/s10493-006-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Methyl Salicylate, A Component of Herbivore-induced Plant Odour, Promote Sporulation of the Mite-pathogenic Fungus Neozygites tanajoae?

Abstract: Blends of volatile chemicals emanating from cassava leaves infested by the cassava green mite were found to promote conidiation of Neozygites tanajoae, an entomopathogenic fungus specific to this mite. Methyl salicylate (MeSA) is one compound frequently present in blends of herbivore-induced plant volatiles (HIPV) as well as that of mite-infested cassava. Here, we investigated the effect of methyl salicylate in its pure form on the production of pre-infective spores (conidia), and the germination of these spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
9
0
5
Order By: Relevance
“…Calvo et al (2002) speculated that seed fatty acids, like linoleic acid, can increase conidial development in Aspergillus by mimicking and/or interfering with signals that regulate fungal sporogenesis. There is evidence that abiotic stresses, such as excess of light, chemicals or mechanical damage, also increase fungal sporulation and/or conidial germination (Hountondji et al 2006). In our results, whenever a stimulatory effect on sporulation was apparent, the corresponding inhibitory effect on growth was absent, negligible or very low (0 to 9%).…”
Section: Discussionmentioning
confidence: 99%
“…Calvo et al (2002) speculated that seed fatty acids, like linoleic acid, can increase conidial development in Aspergillus by mimicking and/or interfering with signals that regulate fungal sporogenesis. There is evidence that abiotic stresses, such as excess of light, chemicals or mechanical damage, also increase fungal sporulation and/or conidial germination (Hountondji et al 2006). In our results, whenever a stimulatory effect on sporulation was apparent, the corresponding inhibitory effect on growth was absent, negligible or very low (0 to 9%).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the fungus is able to time its production of conidia to the presence of actively feeding hosts and not just solely plant cues. Follow up studies demonstrated that a common component of herbivore-induce plant volatiles, methyl salicylate promoted the production of primary conidia but not their germination into secondary capilliconidia (Hountondji et al 2006). This response was isolatedependent and differed from the earlier study, indicating that methyl salicylate is unlikely to be the only factor involved.…”
Section: Variousmentioning
confidence: 99%
“…A chemical factor that facilitates fungal germination and increases insect mortality should promote plant fitness. One potential route already discussed is the role of plant volatiles, particularly those produced as a result of herbivore damage (Hountondji et al 2005(Hountondji et al , 2006. If a fungus can respond to herbivore-induced plant volatiles in a way that enhances the infection rate, such as by increased germination in the presence of the host, then fungal-induced mortality should also increase.…”
Section: Could Plants Manipulate Fungal Entomopathogens For Their Ownmentioning
confidence: 99%
“…The reductions in P. formosa spore viability and in B. bassiana sporulation in the presence of leaves were mainly due to the release of volatile compounds from these organs. Previous studies have reported contradictory effects of plant volatiles, showing either an inhibitory (Hountondji et al 2006) or no effect (Baverstock et al 2005) on fungal sporulation. This inconsistency was also found in the present study.…”
Section: Discussionmentioning
confidence: 93%